PASAT: pathfinder in solar adaptive telescope - Rao, Changhui; Ji, Haisheng; Bao, Hua; Rao, Xuejun; Yang, Jinsheng; Guo, Youming; Zhang, Lanqiang; Zhong, Libo; Fan, Xinlong; Zhang, Qingmin; Li, Cheng; Bian, Qing (Frontiers in Astronomy and Space Sciences, 2024)
In the forefront of quantitative solar physics research using large-aperture ground-based solar optical telescopes, high-contrast observation along with high-accuracy polarimetric measurement in the solar active region are required. In this paper, we propose a novel high-contrast imaging telescope construction with a 60 cm medium aperture, namely, the PAthfinder in Solar Adaptive Telescope (PASAT), in which a deformable secondary mirror is used as the adaptive optical correction device and a symmetrical optical path design is employed, leading to the least Muller matrix polarization instruments. The telescope can provide a high-resolution magnetic field with high accuracy for the solar active regions, as well as high-contrast images with a superior signal-to-noise ratio and photometric accuracy of the solar photosphere and chromosphere. These data will be directly used for a better understanding of the evolution and release of magnetic energy, which will help in improving space weather forecasting. Meanwhile, PASAT will accumulate the relevant techniques for constructing similar, larger solar telescopes in the future.